Svenska kyrkan efter millennieskiftet - Straarup, Jørgen (Religionsvidenskabeligt Tidsskrift, 2015)
Since the year 2000, the Church of Sweden is no longer a function within the Swedish state. It has become a free denomination which actualizes several borderland changes in the Swedish model of religion. The dissolution of the relationship with the state has been discussed and prepared for many years, and it became a reality at the turn of the millennium. The need for a defined relationship with the state or an interface, however, has not diminished, since the Church of Sweden is still the largest popular movement in the country. This change in relation has lead to an intensified cooperation between the Church of Sweden and other churches and denominations. Sedan år 2000 är Svenska kyrkan inte längre en funktion i svenska staten, utan ett fritt trossamfund. Denna relationsförändring aktualiserar en rad nya gränssnitt i den svenska religionsmodellen. Upplösningen av sammanhanget med staten har diskuterats och förberetts under många år och förverkligats i samband med millennieskiftet. Behovet av definierad relation till statsmakten, ett gränssnitt, minskade emellertid inte, eftersom Svenska kyrkan även efter nyårsmorgon 2000 var landets största folkrörelse. Relationsförändringen ledde till ett intensifierat samarbete med andra kyrkor och samfund